Biochemical elucidation of citrate accumulation in Synechocystis sp. PCC 6803 via kinetic analysis of aconitase - Maki Nishii (Nature Portfolio, 2021)
Abstract A unicellular cyanobacterium Synechocystis sp. PCC 6803 possesses a unique tricarboxylic acid (TCA) cycle, wherein the intracellular citrate levels are approximately 1.5–10 times higher than the levels of other TCA cycle metabolite. Aconitase catalyses the reversible isomerisation of citrate and isocitrate. Herein, we biochemically analysed Synechocystis sp. PCC 6803 aconitase (SyAcnB), using citrate and isocitrate as the substrates. We observed that the activity of SyAcnB for citrate was highest at pH 7.7 and 45 °C and for isocitrate at pH 8.0 and 53 °C. The K m value of SyAcnB for citrate was higher than that for isocitrate under the same conditions. The K m value of SyAcnB for isocitrate was 3.6-fold higher than the reported K m values of isocitrate dehydrogenase for isocitrate. Therefore, we suggest that citrate accumulation depends on the enzyme kinetics of SyAcnB, and 2-oxoglutarate production depends on the chemical equilibrium in this cyanobacterium.